Bacterial community analysis of the skin microbiota of cultured Chinese giant salamander infected with Ranavirus - Zhang, Han; Ma, Hongying; Jiang, Wei; Deng, Jie; Yuan, Jianglai; Fang, Cheng; Zhao, Hu; Zhang, Jianlu; Kong, Fei; Zhang, Hongxing; Wang, Qijun (Frontiers in Microbiology, 2024)
Skin microorganisms are an important component of host innate immunity and serve as the first line of defense against pathogenic infections. The relative abundance of bacterial species, microbial community assembly, and secretion of specific bacterial metabolites are closely associated with host health. In this study, we investigated the association between the skin microbiome and Ranavirus, and compared the bacterial community assemblage, alpha and beta diversity, and functional predictions of the skin bacterial assemblage in cultured healthy Chinese giant salamanders (Andrias davidianus) and individuals infected with Chinese giant salamander iridovirus (GSIV or ADRV). To achieve this, we employed 16S rRNA amplicon sequencing. The results identified Proteobacteria, Firmicutes, Bacteroidota, and Actinobacteriota as the dominant phyla in the diseased and healthy groups. Alpha diversity analysis indicated that the skin bacterial community in the diseased group exhibited no significant differences in bacterial community species diversity and lower community species richness compared to the healthy group. Beta diversity suggested that the structure of two group bacterial community was quite different. KEGG pathway analyse and COG function predictions revealed that changes and variations occurred in the metabolic pathways and function distribution of skin bacterial communities in two groups.